2021
DOI: 10.1108/intr-06-2020-0327
|View full text |Cite
|
Sign up to set email alerts
|

The continuation and recommendation intention of artificial intelligence-based voice assistant systems (AIVAS): the influence of personal traits

Abstract: PurposeBased on the post-acceptance model of information system continuance (PAMISC), this study investigates the influence of the early-stage users' personal traits (specifically personal innovativeness and technology anxiety) and ex-post instrumentality perceptions (specifically price value, hedonic motivation, compatibility and perceived security) on social diffusion of smart technologies measured by the intention to recommend artificial intelligence-based voice assistant systems (AIVAS) to others.Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 99 publications
0
22
0
Order By: Relevance
“…To examine common method bias in this self-reported survey research, we employed two methods: (1) Harman's one-factor test (Podsakoff et al ., 2003) and (2) measuring the variance influence factors (VIFs) of the vertical/lateral collinearity and full collinearity (Kock and Lynn, 2012; Lee et al ., 2021). Vertical and latent collinearity is a measure of collinearity among predictor-predictor variables and among predictive variables and a dependent variable, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To examine common method bias in this self-reported survey research, we employed two methods: (1) Harman's one-factor test (Podsakoff et al ., 2003) and (2) measuring the variance influence factors (VIFs) of the vertical/lateral collinearity and full collinearity (Kock and Lynn, 2012; Lee et al ., 2021). Vertical and latent collinearity is a measure of collinearity among predictor-predictor variables and among predictive variables and a dependent variable, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, previous studies have used hedonicism as a major predictor of user behavior on technological systems [62]. With the continuous development of AI technologies, hedonic motivation has been widely used in terms of users' acceptance of AI [63,64], involving applications such as smart banking [48] and smart voice assistants [65], and some scholars have shown that hedonic motivation also significantly influences the social presence of AI chat systems and thus the intentions to use AI chat services [66]. For users, when using AI devices for hedonic motives, these devices can provide benefits by satisfying personal interests and entertainment needs [67], in other words, hedonic motives are the pleasure or joy derived from using the technology or system and are important determinants of users' acceptance and continued use of the technology [68].…”
Section: Hedonic Motivation (Hm)mentioning
confidence: 99%
“…Recent literature has signified the relationship between customer interactions and engagement in purchase intention in AI VAs shopping (Chopra, 2019;Hsieh and Lee, 2021;Lee et al, 2021). McLean et al (2021) explained that customers' cognitive, affective and behavioural engagement leads to positive purchase intention in the AI VAs context.…”
Section: Customer Engagement and Purchase Intentionsmentioning
confidence: 99%